The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1192/bjp.bp.115.167239
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the endophenotypic status of cognition in bipolar disorder: Genetic modelling study of twins and siblings

Abstract: Verbal episodic and spatial working memory capture a modest fraction of the bipolar diathesis. IQ and visual-spatial learning may tap into genetic substrates of non-affective symptomatology in bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Our finding of enhanced performance may be attributable to the non-clinical sources of our sample and the euthymic state of the majority of probands and relatives. The significant familial association for visuospatial ability confirms the recent finding of substantial heritability of visuospatial learning in a twin-family study of a clinical sample of BPD (Georgiades et al, 2016). This finding is also notable given that males tend to outperform females on the PLOT (Gur et al, 2012; Moore et al, 2016), yet the BP-I group still outperforms the controls even though they are only 28% male (versus 47% male in controls).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our finding of enhanced performance may be attributable to the non-clinical sources of our sample and the euthymic state of the majority of probands and relatives. The significant familial association for visuospatial ability confirms the recent finding of substantial heritability of visuospatial learning in a twin-family study of a clinical sample of BPD (Georgiades et al, 2016). This finding is also notable given that males tend to outperform females on the PLOT (Gur et al, 2012; Moore et al, 2016), yet the BP-I group still outperforms the controls even though they are only 28% male (versus 47% male in controls).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have demonstrated poorer performance in line orientation and other tests of visuospatial processing between BPD patients and controls (Frantom et al, 2008; Georgiades et al, 2016; Torres et al, 2010). Our finding of enhanced performance may be attributable to the non-clinical sources of our sample and the euthymic state of the majority of probands and relatives.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Using psychosis as a dimension in grouping the participants, a family study revealed a gradient of performance on the working and declarative memory, executive functions, and attention with the poorest being in probands (i.e., SCH-P, BD-P with psychosis), intermediate in FDR of the psychosis spectrum, and highest in the FDR of the nonpsychotic spectrum disorder, supporting the notion that cognitive function in BD and SCH defines a psychosis continuum [51]. Structural equation modeling of cognitive data from 331 twins/siblings showed that illness state and concordance for BD had a modest impact of verbal episodic memory and spatial working memory on the bipolar diathesis; IQ and visual-spatial learning, however, were associated with genetic diathesis to BD and with nonaffective symptomatology, also supporting the notion of psychosis continuum [52]. …”
Section: Resultsmentioning
confidence: 77%